Attitudes towards lesbianism in sri lankan context - Samaraweera, H.U.S. (University of Jaffna, 2012)
Since social attitudes have established that heterosexuality is the one and only sexual orientation in human beings, homosexuality is defined as a deviant behaviour and excluded from the society. According to literature, homosexuals were excluded from society in the past because of their sexual orientation (Bacchetta, 2007, p.103; Barnett, 2004, p.123; Bersani, 1995, p.8; Dixon, 1983, p. 22). Also according to Bersani (1995), homosexuals hid their sexual identity from the society, because they faced not only physical violence but also emotional violence. First decade this was defined as a mental illness (Bacchetta, 2007). However movements of black people and feminist groups argued for their rights and today most countries see this depends on individuals sexual orientation and make lenient. But still today some other countries have more negative attitudes regarding homosexuality including Sri Lanka. According to the Sri Lankan Penal Code 365(A) homosexuality is a crime. Through this research I studied female homosexality, known as lesbianism, how lesbians see their sexual identity and what kind of social attitudes people have towards them. My main research objective was to identify social attitudes towards homosexual behaviour as literature also proved that lesbians are excluded from Sri Lankan society and point out how social workers could create a more positive social environment for them. The four research questions in this study were: (i) how Sri Lankan society perceived lesbianism and how lesbians perceived this, (ii) would these perceptions differ according to their economic status, gender, education, age and geographical backgrounds; (iii) What are the reasons that influence lesbians to be a lesbian and how society believes the reasons for this sexual behaviour; (iv) Is society aware that homosexuality is a crime according to our Penal Code, what society thinks about this and does society think that homosexuality should be decriminalized?
Keywords: Homosexuality; Sexual orientation; Gender identity; Social work